PENGEMBANGAN MEDIA DIORAMA BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 2 SURODADI - Elsa Dwi Lingga; Armi Yuneti; Cahyo Dwi Andita (LP3MKIL, 2026)
This study aims to develop local wisdom-based Diorama media in Indonesia language learning for fifth-grade students of SD Negeri 2 Surodadi. Testing the validity, practicality, and effectiviness of Diorama media. This type of research is Research and Development with the Four-D development model. The subjects of this study were fifth-grade students of SD Negeri 2 Surodadi. Data collection techniques used observation, interviews, questionnaires, and tests. Based on the validity analysis of Diorama media using the Likert Scale, it shows that the assessment of the language validator is 96.06%, the media validator is 94.33%, and the material validator is 95%. Analysis of the assessment of teacher and student practicality sheets shows that Diorama media meets the criteria of very practical with an average score of 93.83%. Then the analysis of effectiveness assessment obtained an average N-Gam score of 0.77 with a hight category. Based on the results, it was concluded that the local wisdom-based Diorama media was proven to be valid, practical, and effective so that is was suitable for use in Indonesia planguage learning for fifth-grade students of SD Negeri 2 Surodadi